2019
DOI: 10.1177/1357633x19865855
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and efficacy of a web-based family telehealth nutrition intervention to improve child weight status and dietary intake: A pilot randomised controlled trial

Abstract: Introduction Innovative eHealth solutions that improve access to child weight management interventions are crucial to address the rising prevalence of childhood obesity globally. The study aimed to evaluate the feasibility and preliminary efficacy of a 12-week online telehealth nutrition intervention to improve child weight and dietary outcomes, and the impact of additional text messages (SMS) targeted to mothers and fathers. Methods Families with children aged 4 to 11 were randomised across three groups: Tele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
56
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(58 citation statements)
references
References 50 publications
2
56
0
Order By: Relevance
“…Parent-reported and researcher-measured child height and weight data were available from 42 families at baseline and 35 families (83%) at week 12. Baseline characteristics of children and parents who were lost to follow-up, defined as not responding after 3 reminders to complete assessments, were not significantly different from the baseline characteristics of those who completed the follow-up at week 12 [14].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Parent-reported and researcher-measured child height and weight data were available from 42 families at baseline and 35 families (83%) at week 12. Baseline characteristics of children and parents who were lost to follow-up, defined as not responding after 3 reminders to complete assessments, were not significantly different from the baseline characteristics of those who completed the follow-up at week 12 [14].…”
Section: Resultsmentioning
confidence: 99%
“…This was a secondary analysis of data from a pilot randomized controlled trial that aimed to investigate the feasibility of a 12-week Web-based family lifestyle intervention to support parents in improving their child’s weight status and eating habit [14]. The intervention group received 2 semistructured telehealth consultations (online video consultations, attended by at least one parent and the index child) with Accredited Practising Dietitian, access to the Back2basics Family program website [15], a Facebook group, and additional evidence-based short message service (SMS) text messaging targeted to the parents.…”
Section: Methodsmentioning
confidence: 99%
“…Of these, 7894 records were excluded at the title and abstract screening stage, and 97 full text records were assessed for eligibility ( Figure 1 ). A total of 84 of the 97 full text records were excluded for the following reasons: 26 did not measure smoking, nutrition, alcohol consumption, physical activity, and obesity outcomes; 23 did not use any form of video counseling intervention; 19 involved group video counseling and not individual video counseling [ 37 - 54 ]; 3 were protocol papers [ 55 - 57 ]; 8 were not randomized studies [ 58 - 65 ]; 2 studies were ongoing [ 32 , 66 ]; 1 was a conference abstract [ 67 ]; and 2 studies described a multicomponent intervention, and it was not possible to isolate the effect of real-time video counseling [ 68 , 69 ]. The remaining 13 eligible studies were included in the review.…”
Section: Resultsmentioning
confidence: 99%
“…In this issue, Chai et al detailed the three‐stage development of a bank of text messages targeted to parents of primary school‐aged children, designed to support improvement in child eating behaviours . After evaluation by health experts and parents based on clarity, usefulness and relevance, a bank of 48 text messages were retained for use as a component of a future family‐based nutrition intervention . Lombard et al previously reported in this journal the protocol for the Communicating Health (CH) study, which focused on using social media for health communication in young adults.…”
Section: Developing Intervention Componentsmentioning
confidence: 99%
“…21 After evaluation by health experts and parents based on clarity, usefulness and relevance, a bank of 48 text messages were retained for use as a component of a future family-based nutrition intervention. 22 Lombard et al 23 previously reported in this journal the protocol for the Communicating Health (CH) study, which focused on using social media for health communication in young adults. CH was a four phase, iterative study aimed at understanding young adults use of social media for obtaining dietary health information, co-creating healthy eating messages and communication strategies, evaluating the messages, and developing tools and resources for use by stakeholders and researchers in this field.…”
Section: Developing Intervention Componentsmentioning
confidence: 99%